2014
DOI: 10.1007/s00253-014-5575-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and antiviral products of marine organisms

Abstract: Marine organisms including bacteria, fungi, algae, sponges, echinoderms, mollusks, and cephalochordates produce a variety of products with antifungal activity including bacterial chitinases, lipopeptides, and lactones; fungal (−)-sclerotiorin and peptaibols, purpurides B and C, berkedrimane B and purpuride; algal gambieric acids A and B, phlorotannins; 3,5-dibromo-2-(3,5-dibromo-2-methoxyphenoxy)phenol, spongistatin 1, eurysterols A and B, nortetillapyrone, bromotyrosine alkaloids, bis-indole alkaloid, ageloxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 123 publications
1
57
0
2
Order By: Relevance
“…Recently many studies have evidenced the great potential of antarctic fungi in producing bioactive secondary metabolites (Cheung et al . ; Henríquez et al . ; Gonçalves et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently many studies have evidenced the great potential of antarctic fungi in producing bioactive secondary metabolites (Cheung et al . ; Henríquez et al . ; Gonçalves et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently many studies have evidenced the great potential of antarctic fungi in producing bioactive secondary metabolites (Cheung et al 2014;Henr ıquez et al 2014;Gonc ßalves et al 2015). In this context, the application of compounds of microbial origin became an environmentally Letters in Applied Microbiology 67, 64--71 © 2018 The Society for Applied Microbiology friendly alternative to the use of chemicals (Dayan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that it plays an important role in innate immunity against yeast in the internal circulatory system of the lamprey. A repertoire of natural bioactive compounds has been isolated from marine organisms which showed promising medicinal potential (Cheung et al 2014). The marine lectins exhibited strong antimicrobial activity as aforementioned, implying that they can be potential candidates for drug design and development in the future.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Currently, the plant‐related pharmacological formulations are being highly ranked for viral infections (Newman & Cragg, ). Many studies showed that compounds isolated from a marine organism expressed in vitro activity (Jha & Zi‐rong, ), but only the didemnins (compounds derived from a marine plant) have produced activity in vivo (Cheung et al, ). These are cyclic depsipeptides isolated from Tridelemnum solidum (Didernnidae, family); some of the didemnins exhibit antiviral activity (Vera & Joullie, ).…”
Section: Introductionmentioning
confidence: 99%